The CJEU broadens the scope of European SPCs, but shortens validity of its duration in certain Member States - Daniel Acquah (Oxford University Press, 2022)
The Court of Justice of the European Union (CJEU) has clarified that, where a medicinal product has been the subject of a marketing authorization (MA) within the European Economic Area (EEA), before that granted in a Member State of the European Union (EU), and even before the Member State’s accession to the EU, the EEA MA must be taken into account for the purpose of determining the duration of the supplementary protection certificate granted in the EU.